2009
DOI: 10.1160/th08-08-0551
|View full text |Cite
|
Sign up to set email alerts
|

Risk of venous thromboembolism with rheumatoid arthritis

Abstract: Rheumatoid arthritis is not generally considered to be a risk factor for venous thromboembolism (VTE), although abnormalities of coagulation factors have been found in patients with rheumatoid arthritis. Sparse data in a few patients suggest that patients with rheumatoid arthritis may have higher rates of VTE. The purpose of this investigation was to determine if the incidences of pulmonary embolism (PE) and deep venous thrombosis (DVT) are increased in hospitalized patients with rheumatoid arthritis. The numb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
82
0
10

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(95 citation statements)
references
References 22 publications
3
82
0
10
Order By: Relevance
“…Furthermore, the increased incidence of VTE in patients with risk factors for arterial cardiovascular events points too to a common pathogenesis (6). Indeed, a number of studies, with different design and in various clinical settings, have shown an increased risk of VTE associated with most of the classic or novel risk factor for ischaemic cardiovascular disease (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) (ǠTable 1).…”
Section: The Association Between Venous and Arterial Thrombosismentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the increased incidence of VTE in patients with risk factors for arterial cardiovascular events points too to a common pathogenesis (6). Indeed, a number of studies, with different design and in various clinical settings, have shown an increased risk of VTE associated with most of the classic or novel risk factor for ischaemic cardiovascular disease (7)(8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22) (ǠTable 1).…”
Section: The Association Between Venous and Arterial Thrombosismentioning
confidence: 99%
“…In particular, acute reactions to infectious agents are associated with an increased risk of both arterial ischaemic events and VTE and are accompanied by both arterial and venous endothelial dysfunction (40,43,44); increased circulating levels of some biomarkers of endothelial dysfunction, like endothelial microparticles or P-selectin, are associated with both an enhanced risk of cardiovascular events and of VTE (45)(46)(47); recent data have shown in patients with VTE an increase of circulating fibronectin, an endothelium-released plasma factor previously shown to correlate with arterial endothelial dysfunction (48,49); several other clinical conditions characterised by an impaired arterial endothelial function, like airpollution, chronic HIV infection, a family history of myocardial infarction, the metabolic syndrome, rheumatoid arthritis and microalbuminuria, have been reported to be associated not only with an increased risk of arterial events but also of venous thrombosis (12,14,16,19,21,22,(50)(51)(52).…”
Section: (ǡTable 2)mentioning
confidence: 99%
“…74,75 The incidence of those comorbidities can be associated with classic risk factors that affect the general population and with specifi c aspects of RA. [74][75][76] In general, the following fi ndings contribute to increase the risk of thromboembolism: lower mobility consequent to joint lesions; hospitalizations with prolonged bed confi nement; more advanced age of most arthritic patients; compression of the venous system adjacent to a joint with huge joint effusion; and obesity.…”
Section: Venous Thrombosis and Pulmonary Embolismmentioning
confidence: 99%
“…74,75 The incidence of those comorbidities can be associated with classic risk factors that affect the general population and with specifi c aspects of RA. [74][75][76] In general, the following fi ndings contribute to increase the risk of thromboembolism: lower mobility consequent to joint lesions; hospitalizations with prolonged bed confi nement; more advanced age of most arthritic patients; compression of the venous system adjacent to a joint with huge joint effusion; and obesity. 74 Patients with RA have changes in the coagulation parameters and in the fi brinolytic system, 77 the most common fi ndings being as follows: increased platelet count; increased platelet activation markers; and increased thrombin markers, such as thrombin-antithrombin complexes and prothrombin fragments.…”
Section: Venous Thrombosis and Pulmonary Embolismmentioning
confidence: 99%
See 1 more Smart Citation